2022
DOI: 10.3389/fpls.2022.917354
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Defense Trade-Offs Induced by Long-term Overgrazing Could Act as a Stress Memory

Abstract: Long-term overgrazing (OG) is one of the key drivers of global grassland degradation with severe loss of productivity and ecosystem functions, which may result in stress memory such as smaller stature of grassland plants. However, how the OG-induced stress memory could be regulated by phytohormones is unknown. In this study, we investigated the changes of four phytohormones of cloned offspring of Leymus chinensis that were developed from no-grazing (NG) plants and OG plants with a grazing history of 30 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In this regard, Dai et al [ 16 ] reported that the moderate grazing promoted the root biomass of Kobresia meadow (BGB) in the northern Qinghai-Tibet pastures, which corroborates with our findings. Thus, the adaptive response of plants might occur in which they tend to increase their root development to survive [ 17 ]. Also, during the April-May period, snow melting occurs in the pasturelands of Kashmir Valley which naturally favors and promotes the growth and development of BGB.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Dai et al [ 16 ] reported that the moderate grazing promoted the root biomass of Kobresia meadow (BGB) in the northern Qinghai-Tibet pastures, which corroborates with our findings. Thus, the adaptive response of plants might occur in which they tend to increase their root development to survive [ 17 ]. Also, during the April-May period, snow melting occurs in the pasturelands of Kashmir Valley which naturally favors and promotes the growth and development of BGB.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, its supernatant was used for the determination of three endogenous hormone (GA3, IAA, and ABA) contents using HPLC-MS/MS. The chromatographic conditions were set according to Qu et al [17].…”
Section: Determination Of Hormone Contentsmentioning
confidence: 99%
“…For example, livestock overgrazing reduces individual plant height, shortens and narrows leaves, and decreases stem length [14][15][16]. Except for the immediate responses to trampling and herbivory in the field, some studies have demonstrated that these dwarf characteristics contribute to the regulation of photosynthetic and hormonal pathways [15,17]. The dwarf characteristics may help plants to escape herbivores as much as possible, which is supposed to be a grazing avoidance strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation